Green Synthesis, Structural Insights, and Antimicrobial Potential of Zinc Oxide Nanoparticles Synthesized via Sustainable Method - Kumar, Vishnu. K.; M.V, Manjusha; Francis, Shebin; P.R, Shehsadi; Varghese, Princy (Current Physical Chemistry, 2025)
BackgroundGreen synthesized nanoparticles have gained wide interest in today’s world due to their inherent features like rapidity, eco-friendliness, and cost-effectiveness. In this study, zinc oxide (ZnO) nanoparticles were synthesized using an aqueous extract of Ixora coccinea leaves. X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) studies were used to analyze the structural and morphological properties of prepared Zinc Oxide nanoparticles.MethodsThe sol-gel method of synthesis via the green route was introduced to synthesize pure Zinc oxide nanoparticles. Silver-doped zinc oxide nanoparticles were also prepared using the same method.ResultThe XRD studies showed the crystalline nature and revealed the purity of Zinc Oxide nanoparticles. The specific functional groups responsible for reduction, stabilization, and capping agents present in the nanoparticles were examined using Fourier Transform Infrared Spectroscopy (FTIR) spectroscopy. The bacterial destruction was better for ZnO nanoparticles than reported for plant extracts and standard drugs.ConclusionThis study proves that zinc oxide nanoparticles contain natural anti-microbial agents through green synthesis, which may serve to produce drugs for antimicrobial therapeutics.
Keywords: crystal structure